Composition and diversity of tree species after fire disturbance in a lowland tropical forest in East Kalimantan, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Sakai A, Arbain, Sugiarto, Rahmawati K, Mirmanto E, Takahashi M, Ueda A. 2022. Composition and diversity of tree species after fire disturbance in a lowland tropical forest in East Kalimantan, Indonesia. Biodiversitas 23: 1576-1587. Lowland dipterocarp forests in East Kalimantan have suffered severe forest fires after prolonged drought at least twice in recent decades. We investigated species richness, stand structure and species composition in Sungai Wain Protection Forest using circle plots (each 0.04 ha) along multiple long transects (0.5 - 4.5 km long) from the edge to the interior of this forest. The impact of forest fires remained in the form of significantly smaller tree sizes in burnt areas, although species richness and the number of stems appeared to be recovering. NMDS (non-metric multidimensional scaling) ordination revealed that the species composition of burnt areas was still considerably different from that of intact forest. However, nearly 20 years have elapsed, suggesting that it takes a long time for species composition to recover, if at all. The species composition was affected by the basal area ratio of pioneer trees, the basal area ratio of dipterocarp trees and maximum diameter at breast height, in order of its strength. Distance from the edge of the Protection Forest also had a minor effect on species composition, suggesting that forest fires had damaged marginal areas of the forest.